KELEMBAGAAN DALAM SISTEM PERTANIAN PADI SEHAT - Indriana, Hana; Tonny, Fredian; K. Pandjaitan, Nurmala (Sodality: Jurnal Sosiologi Pedesaan, 2012)
Organic agriculture system has already developed and sustain until today in the middle of agricultural modernization. It's become an alternative to build sustainable agriculture and institutional support become important element to build it. Related to that, the objective of this research was to analysis how is an agriculture sustainability will be built supported by sustainable institutions in organic agriculture system. The study is a sociological research which assumed itself into constructivist paradigm, which is a qualitative exploration, with specific cases using multi-method. The research was held on October 2008 until February 2009 and located in Ciburuy Village with paddy peasant community as the unit of analysis. The result of the research shows that organic agriculture system in Ciburuy Village is healty rice agriculture system which produce SAE branded rice (Healthy, Save, and Delicious). Technically, the system has not yet became pure organic agriculture which free of synthetic chemical because the using of chemical fertilizer. Nevertheless, a process and also an implementation of the system related to the principles of organic agriculture system. So that, production techniques, social relationships, and the rules that embedded in were built to build agriculture sustainability. With the development of healthy rice farming systems, do not change a working relationship system of division of labor and wage system between tenant farmers and farm laborers. Similarly at harvest activity. The differences appear in the presence of mechanisms that shape institutional providers of fertilizer and pesticides, institutional Cooperative Farmers Group "Lisung Kiwari", institutional post-harvest, and institutional distribution of rice SAE as a product of healthy rice. Keywords : organic agriculture system, institutions sustainability, sustainable                     agriculture, people center development